Bancarizing with credit cards: Experimental evidence on interest rates and minimum payments elasticities for new clients - Enrique Seira; Sara G. Castellanos; Diego J. Jiménez Hernández (Banco de México, 2015)
We study the bancarization of marginal borrowers using credit cards and document that this process is difficult: default risk is substantial, returns heterogeneous, and account closings common. We also take advantage of a randomized control trial that varied interest rates and minimum payments in a very wide range. Against our hypothesis, we find that default risk is very insensitive to (randomized) large changes in interest rates and minimum payments. This could imply that regulating these contract terms may not necessarily "protect" consumers against default and that moral hazard in this market is negligible on average.
Keywords: D14; D18; D82; G21; 330; Credit cards; Development finance; Consumer behavior; Mexico